2008
DOI: 10.1111/j.1365-2672.2008.03783.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycated protein modulates the colonic microbiota towards a more detrimental composition in ulcerative colitis patients and non-ulcerative colitis subjects

Abstract: Aim:  To investigate the effect of native, heated and glycated bovine serum albumin (BSA) on the ulcerative colitis (UC) and non‐UC colonic microbiota in vitro. Methods and Results:  Continuous flow culture (CFC) models of the human colonic microbiota inoculated with faeces from UC and non‐UC volunteers were maintained on BSA as growth substrate. Changes in bacterial populations and short‐chain fatty acids were determined. UC and non‐UC microbiota differed significantly in microbial populations, with elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 32 publications
3
83
0
Order By: Relevance
“…The known detrimental genotoxic (Attene- Ramos, Wagner, Plewa, & Gaskins, 2006), T-cell activation enhancing (Miller & Richardson, 2012) and colonic microbiome shaping effects of produced hydrogen sulphide may be promoted by its unhindered diffusion across lipid membranes (Mathai et al, 2009) and may be indirectly influenced by the dietary effects on the abundance of SRP (e.g. Mills et al, 2008). Another member of the intestinal flora closely related to SRP is B. wadsworthia.…”
Section: 11mentioning
confidence: 97%
“…The known detrimental genotoxic (Attene- Ramos, Wagner, Plewa, & Gaskins, 2006), T-cell activation enhancing (Miller & Richardson, 2012) and colonic microbiome shaping effects of produced hydrogen sulphide may be promoted by its unhindered diffusion across lipid membranes (Mathai et al, 2009) and may be indirectly influenced by the dietary effects on the abundance of SRP (e.g. Mills et al, 2008). Another member of the intestinal flora closely related to SRP is B. wadsworthia.…”
Section: 11mentioning
confidence: 97%
“…Interestingly, Fernandes et al (104) have recently confirmed that methane production and carriage of detectable Archaea (mainly methanogens in human subjects) are inversely related to BMI and that methanogenesis appears to allow more efficient production and absorption of SCFA from dietary fibre fermentation. While the ecological processes regulating the relative abundance of gut SRB and methanogens are not fully understood, ingestion of fermentable fibre increases methanogenesis in CH 4 -producing subjects, while sulphate or dietary protein appear to stimulate the numbers of SRB and presumably their metabolic activities within the gut microbiota (105)(106)(107)(108)(109) .…”
Section: Diet Can Bring Out the Worst Of Microbial Behaviours: Microbmentioning
confidence: 99%
“…In addition, AGEs also infl uence the normal gut fl ora (95), reducing the amounts of "good bacteria" (96) and compromising nutrient's and phytochemicals' absorbtion.…”
Section: The Role Of Oxidative Stressmentioning
confidence: 99%